Exploring the impact of internal communication on employee engagement with a major change strategy within the context of an NHS Hospital Trust. - Moore, Peter (2008)
Managing change is a complex process in any organisation, not least within the National Health Service. Effective communication channels are vital to ensuring that the organisations strategy and objectives reach those employees who can actually implement change. Existent within the academic research are many examples of effective internal communication and though there are constraints due to the context this should not prevent greater levels of adoption. Research on employee engagement also places internal communication high on the list of drivers encouraging engagement. Through adopting an approach which gains benefit from both quantitative and qualitative research this study gathered a dataset which has a breadth across the organisation and a depth of employee attitudes and feelings. From this research we have identified key themes relating to the effectiveness of commonly used communication tools and observed how this impacts on a management team keen to get their message of change across to a wide and diverse internal public. Adopting the recommendations of the research should be the first step in improving internal communication, and a series of follow on audits need to be planned to measure effectiveness of this change.